El pobrecito Manuel Pascual: almanaques burlescos entre el ingenio, la literatura y el negocio - Ana Isabel Martín Puya (Cuadernos de Ilustración y Romanticismo)
In this work, we introduce the path of a literary character («el pobrecito Manuel Pascual») that becomes a fictional author of burlesque almanacs and appears in some works published by distinctive authors between 1737 and 1745. Reiteraition of motives and intertextual dialogue between these almanacs allow us to increase our knowledge on editorial practises and burlesque almanacs; specially, about authorial strategies and reception. It also provide us unanswered questions to solve in future works.